MENELAAH HUKUM AHLI WARIS PENGGANTI DALAM ILMU FARAIDH - Zulfan Ependi Hasibuan (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2018)
In the Compilation of Islamic Law referred to as the heirs of the clergy is in accordance with the provisions contained in article 185, namely: Heirs who died first than the heirs, their position can be replaced by their children, and the substitute heirs cannot exceed the heirs the equivalent of the one being replaced. Whereas community understanding in some cases of research about substitute heirs, namely heirs who replaced the position of the deceased father before grandparents.